Odpowiedzi

2010-01-21T22:20:08+01:00
1.a) 3
b)2x
c)2pq
d)3a+2b
e)2p-r
f)x-¹/₄y
g)¹/₃a-b
h)x+y+¹/₅
i)3d-¹/₂
j)2b-4a
2. Pierwsze wpisuj po kolei od góry: 2y-3xy, -2x²+3x³,x-³/₂x²
Drugie -||- 5-ab, -b²+¹/₅ab³, ab-¹/₅a²b²
3.a)196(295-296)=-196
b)2,8(8,2+1,8)=28
c)149,9(1+8-10)=-149,9
d)14¹/₂₁(⁸/₁₇+⁹/₁₇)=14¹/₂₁
e)¹/₁₁₁(¹/₃*¹/₈+²³/₂₄)=¹/₁₁₁
f)7(7²+1)/7²+1=7
  • Roma
  • Community Manager
2010-01-21T22:36:47+01:00
1.
a) 6x - 9y = 3(2x - 3y)
b) 4xy - 6x = 2x(2y - 3)
c) 12p²q - 2pq = 2pq(6p - 1)
d) -9a² - 6ab = -3a(3a + 2b)
e) p - ½r = ½(2p - r)
f) 4x - y = 4(x - ¼y)
g) a - 3b = 3(⅓ a - b)
h) 5x + 5y + 1 = 5(x + y + ⅕)
i) 6cd² - cd = 2cd(3d - ½)
j) a²b - 2a³ = ½ a²(2b - 4a)

2.
6x²y - 9x³y = 3x²(2y - 3xy)
6x²y - 9x³y = -3y(-2x² + 3x³)
6x²y - 9x³y = 6xy(x - ³/₂ x²)

5a²b² - a³b³ = a²b²(5 - ab)
5a²b² - a³b³ = -5a²(-b² + ⅕ ab³)
5a²b² - a³b³ = 5ab(ab - ⅕ a²b²)

3.
a) 196*295 - 196*296 = 196*(295 - 296) = 196*(-1) = -196
b) 2,8*8,2 + 1,8*2,8 = 2,8*(8,2 + 1,8) = 2,8*10 = 28
c) 149,9 + 149,9 * 8 - 1499 = 149,9*(1 + 8 - 10) = 149,9 * (-1) = -149,9
d) 14¹/₂₁ * ⁸/₁₇ + 14¹/₂₁ * ⁹/₁₇ = 14¹/₂₁ * (⁸/₁₇ + ⁹/₁₇) = 14¹/₂₁ * ¹⁷/₁₇ = 14¹/₂₁ * 1 = 14¹/₂₁
e) ¹/₃₃₃ * ⅛ + ¹/₁₁₁ * ²³/₂₄ = ¹/₁₁₁*(⅓* ⅛+ 1*²³/₂₄) = ¹/₁₁₁ *( (¹/₂₄ + ²³/₂₄) = ¹/₁₁₁ * 1 = ¹/₁₁₁
f) 7³ + 7 / 7² + 1 = 7*(7² + 1) / 7² + 1 = 7